Value chain analysis of sardines (Sardinella spp.) in Guiwanon, Nueva Valencia, Guimaras. - Libanan, Azel Ann E.
The sardine fishery provided food, employment, and income to the residents of barangay Guiwanon in the municipality of Nueva Valencia, Guimaras Province. This study analyzed the value chain of sardines in Guiwanon by describing the flow of sardines from the fishers to the consumers, identifying the different actors involved and the linkages between actors in the chain, determining the costs incurred, gross margin, and net returns received by the actors, determining benefit distribution, describing the roles performed by men and women in sardine value chain, and identifying the problems faced by men and women in sardine value chain, and identifying the problems faced by the actors in sardine industry. The data was collected through personal faced by the actors in sardine industry. The data was collected through personal interviews with 13 sardines fishers, nine sardines fisher-processors, five dried sardines processors, and 14 dried sardine traders. The fishers and fisher-processors caught a total of 253,226 kilograms of sardines in a year, where most were sold to processors of dried sardines. The processors received the highest net returns of P35.80 per kilogram while the fishers received the lowest net returns of P11.98 per kilogram. Fishers were generally price takers and the market for sardines in influenced by the processors. The net added value of sardines increases as they undergo transformation and as they pass the different market actor in the value chain. Men performed most of the tasks involved in fishing that require physical strength (such as carrying and unloading) while the women performed most processing activities (such as dying, sorting, and packing). Proper implementation of fishing regulations, new processing techniques, and new market outlet for sardine products are recommended to increase efficiency in sardine value chain